A new proposal to evaluate the healing of open skin wounds: volumetry - Paulo,Danilo Nagib Salomão (2011)
PURPOSE: To present a new proposal to evaluate the healing of an open subcutaneous and skin wound, which we termed "volumetry". METHODS: A total of 32 circular wounds were performed in the subcutaneous tissues and skin of four feet of pigs (8 each). Each wound had about 1 cm in diameter and was 0.2 cm deep. Volume was calculated from the wound filled with saline and mass Xantopren. With the aid of a magnifying glass and local lighting, the liquid was dripped with a micropipette inside the wound until complete fullness. Volume repletion was calculated in microliters, corresponding to the volume of the wound. The mass of Xantopren was placed inside the wound to obtain a mold of the lesion. Mold volume was calculated using the formula of the volume of a cylinder closest resembling a geometric figure with mold. RESULTS: The calculation of wound volume was possible with both Xantopren and mold techniques. Volume as calculated by micropipette was 119.37 ± 30.87 microliters while the volume calculated by mold was 122.41 ± 33.90 mm3 (p=0.79). CONCLUSIONS: Volumetry in pig feet is simple and reproducible. Volumetry perfomed with saline did not differ from the volumetry with mass Xantopren. This method may be a useful tool to help evaluate the healing of open skin wounds in experimental and clinical research.